THE ROLE OF PROBIOTICS AS ADJUVANT THERAPY IN INFLAMMATORY CARDIOVASCULAR DISEASES - Yosephi, Valensa; Syakdiyah, Noer Halimatus; Atmaja, Peter Yustian; Soegiarto, Gatot (Jurnal Biosains Pascasarjana, 2024)
Cardiovascular diseases are the leading cause of death worldwide. Probiotics are live microorganisms that can provide health benefits to the host when administered in adequate amounts. The anti-inflammatory effects of probiotics were initially studied in Crohn's disease (CD) and ulcerative colitis (UC). This research aim to provide scientific evidence and explanation on the effects of probiotic administration as adjuvant therapy for inflammatory diseases in cardiovascular health. The study employed a descriptive approach using the systematic literature review method on PubMed, Scopus, SAGE, and Web of Science. A total of 13 articles were included in this study. The probiotics used included Bifidobacterium in one clinical trial, Lactobacillus in eight clinical trials, Enterococcus in one clinical trial, a combination of Bifidobacterium and Lactobacillus in one clinical trial, and a combination of Lactobacillus and Propionibacterium in one clinical trial.